Pengaruh Motivasi dan Mental Berwirausaha terhadap Minat Berwirausaha Mahasiswa Program Pendidikan Ekonomi Universitas Bhinneka PGRI Tulungagung Tahun Akademik 2024/2025 - Azizah, Ismiatul; Anasrulloh, Muhammad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This research is motivated by the increasing lack of job opportunities in the formal sector, while the number of graduates continues to rise each year. Additionally, members of Generation Z tend to choose jobs that align with their passion and skills, which contributes to the growing unemployment rate. The purpose of this study is to determine the influence of motivation and entrepreneurial mindset on the entrepreneurial interest of students in the Economics Education Study Program, semesters 6 and 8, at Universitas Bhinneka PGRI. The variables in this study consist of motivation (X1) and entrepreneurial mindset (X2) as independent variables, and entrepreneurial interest (Y) as the dependent variable. Higher levels of both internal and external motivation, as well as a strong entrepreneurial mindset, are expected to positively influence one's interest in entrepreneurship. Conversely, low motivation and a weak entrepreneurial mindset may result in decreased entrepreneurial interest. This research uses a quantitative approach with multiple linear regression analysis. The sample consists of 67 respondents from the 6th and 8th semesters of the Economics Education program at Universitas Bhinneka PGRI. Data was collected using a questionnaire distributed via Google Forms through WhatsApp. The data analysis was conducted using SPSS for Windows version 25. The results of the study show that the regression coefficient for the motivation variable (X1) is 0.782, indicating a positive and significant influence on entrepreneurial interest (Y). The entrepreneurial mindset variable (X2) has a regression coefficient of 0.228, also showing a positive and significant effect on variable Y. Simultaneously, the influence of motivation and entrepreneurial mindset on entrepreneurial interest is significant, with an F-value of 188.762 and a significance level of 0.00 (< 0.05). Therefore, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected.